2020
DOI: 10.4103/ija.ija_121_20
|View full text |Cite
|
Sign up to set email alerts
|

The management of patients with placenta percreta: A case series comparing the use of resuscitative endovascular balloon occlusion of the aorta with aortic cross clamp

Abstract: Due to the rising caesarean section (CS) rate, there has been an increase in placenta percreta (PP) cases. Resuscitative endovascular balloon occlusion of the aorta (REBOA) use has been successful in obstetric surgery for PP. In our institution, it has been introduced for prophylactic and therapeutic management in patients with PP. In our environment, the risks, benefits, and associated cost of REBOA use needed to be determined. In this case series, we report on five patients with PP where REBOA or aortic cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The reported data combine both prophylactic and emergent placements of REBOA, with reported studies conducted outside the USA. [18][19][20][21] Ordoñez et al 21 reported on the experience at a Colombian level I trauma center which prophylactically used REBOA in 12 women undergoing an elective cesarean section for morbid placentation with a median estimated blood loss (EBL) of 1500 mL. The authors found the use of REBOA decreased intraoperative blood loss and the number of PRBCs transfused, without REBOA-associated complications.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported data combine both prophylactic and emergent placements of REBOA, with reported studies conducted outside the USA. [18][19][20][21] Ordoñez et al 21 reported on the experience at a Colombian level I trauma center which prophylactically used REBOA in 12 women undergoing an elective cesarean section for morbid placentation with a median estimated blood loss (EBL) of 1500 mL. The authors found the use of REBOA decreased intraoperative blood loss and the number of PRBCs transfused, without REBOA-associated complications.…”
Section: Open Accessmentioning
confidence: 99%
“…The reported data combine both prophylactic and emergent placements of REBOA, with reported studies conducted outside the USA. 18–21 …”
Section: Introductionmentioning
confidence: 99%
“…Although neuraxial anaesthesia (NA) has advantages over other surgical techniques among pregnant woman in terms of the risk of maternal pulmonary aspiration and neonatal results,[ 1 ] general anaesthesia (GA) is routinely used as the standard anaesthetic method in some centres for PAS patients. [ 2 3 ] This is especially true in developing countries where the availability of PAS fixed multidisciplinary teams (PAS team) are often lacking. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%